Permafrost Distribution in Peatlands of West-Central Canada During the Holocene Warm Period 6000 Years BP - Zoltai, Stephen (Géographie physique et Quaternaire, 1995)
ABSTRACTThe extent and distribution of permafrost in peatlands 6000 years ago was investigated in the present discontinuous and continuous permafrost zones of west-central Canada. Permafrost peatlands were cored at 161 locations and the floristic composition of the peat was determined from macrofossil analysis. The reconstructed paleoenvironments were used to indicate the presence or absence of permafrost at the time of peat formation. Chronological control was provided by radiocarbon dating of substantial changes in the peat sequences and by dates of basal peat deposits. Peatland formation began after glacial ice disappeared from the land surface of west-central Canada. Macrofossils indicate that most peatlands were fens without permafrost at 6 ka, except in the far north. Permafrost was already present in many areas of the Arctic, and peat accumulation occurred under permafrost conditions. In the southern area, permafrost development in peatlands began about 4 ka as the middle Holocene warm period came to a close. Permafrost development in the fens was associated with the development of a Sphagnum-dominated surface on the fens, caused by the onset of a cooler and moister climate. The insulation provided by the surface peat layer and by the associated tree cover initiated permafrost development in small lenses that coalesced into large permafrost bodies according to the prevailing climatic conditions. At the target date, 6 ka, permafrost was present in some peatlands, but the distribution zones shifted 300 to 500 km to the north, relative to the present zonation. It is estimated that this corresponds to a mean annual temperature that was about 5°C warmer than at present.